IS THE SHANGHAI COOPERATION ORGANIZATION MAKING A “NATO OF THE EAST”? - Muhammad Naveed Akhtar ,Dr. Faisal Javaid (Pakistan Journal of International Affairs, 2021)
Shanghai Cooperation Organization (SCO) is the largest regional origination in which Russia and China are founding members and recently Iran’s bid for full membership has been approved during the 21st summit of the SCO. These countries are against American hegemony and covertly and overtly demonstrate their concerns. SCO has been conducting military exercises regularly since 2002. Improving Strategic partnership between China and Russia, the presence of Iran, and military exercises of the SCO are matters of concern for the West. Some western scholars labeled it as “NATO of the East” and assessed it as an emerging military bloc. According to official documents and statements, SCO is a political and security organization based on cooperation and partnership and follows a non-interference policy. Does SCO contain components of a military alliance? Is SCO a military bloc or on the way to becoming in the future? This paper evaluates the SCO according to the theoretical concept of a military alliance besides comparative analysis of the SCO with NATO.